Comparative biomechanics of Australopithecus sediba mandibles. Issue 100 (November 2016) - Daegling, David J.; Carlson, Kristian J.; Tafforeau, Paul; de Ruiter, Darryl J.; Berger, Lee R.
Abstract: Fossils attributed to Australopithecus sediba are described as having phylogenetic affinities with early Homo to the exclusion of other South African australopiths. With respect to functional anatomy of mastication, one implication of this hypothesis is that A. sediba mandibles should exhibit absolutely and relatively reduced stiffness and strength in comparison to Australopithecus africanus and Paranthropus robustus jaws. Examination of cortical bone distribution in the MH 1 and MH 2 mandibles of A. sediba (evaluated against samples of Pan, early and modern Homo as well as A. africanus and P. robustus ) indicate that the A. sediba mandibular corpus was geometrically similar to other South African australopiths. In particular, enhanced torsional rigidity is characteristic of all South African australopiths including A . sediba . These findings are consistent with a hypothesis that masticatory mechanics may have been similar to other australopiths (and distinct from exemplars of early Homo ), and as such suggest that A. sediba's mandibles were functionally suited to consume hard and tough objects. Recent mechanical modeling of the A. sediba cranium, however, has been interpreted as indicating that this species was relatively poorly adapted to produce large bite forces and likely experienced relatively modest strains in its facial skeleton. This paradox – that the cranium signals a departure from the australopith morphotype whereas the mandibles conform to a hypodigm of australopith grade – can be resolved, in part, if it is acknowledged that mechanical performance variables offer imperfect insight into what constitutes feeding adaptations.